Multiple members of the E2F transcription factor family are the products of oncogenes. - Xu, G (1995)
The retinoblastoma gene product (pRB) is a known tumor suppressor, capable of arresting growth in mid-to-late G1. Part of its growth suppression action arises from interaction(s) with one or more members of the E2F family of transcription factors. These proteins most likely contribute to progression from G0 to S phase in mammalian cells, and pRB binding most likely inhibits aspects of their suspected growth-promoting function. Given their growth-stimulating potential, we asked whether one or more E2F alleles can function as oncogenes. Uncloned pools of NIH 3T3 cells producing the pRB binding target E2F-1, E2F-2, or E2F-3 grew in semisolid medium. In addition, they grew to much higher saturation density than controls. From the study of cells producing selected E2F-1 mutant species, it appears that E2F DNA-binding function contributes to, and pRB/E2F binding suppresses, soft-agar growth. Thus, three E2F family members can act as oncogene products, suggesting that part of the normal role of pRB is to down-modulate this potential activity.